Peran Sistem Informasi Akuntansi dalam Pengelolaan Dana Infak - Nursetiana, Herni; Pangestu, Feby Risqi; Aji, Gunawan (Budgeting: Jurnal Akuntansi Syariah, 2024)
Accounting Information Systems (AIS) are very important for various aspects of financial management, including infaq fund management in the digital era. One of the factors that can hinder the potential destruction of infaq at this time is the low level of public trust in infaq management organizations. This research aims to find out how technology can be used to manage infaq funds more efficiently and the benefits of implementing an accounting information system in increasing transparency and accountability in infaq fund management. The method used in this research is descriptive with a qualitative approach. The data analysis technique in this research was carried out by categorizing data, filtering data, and presenting data designed narratively. The results of this research conclude that the Accounting Information System is very important in increasing transparency and accountability in the management of infaq funds by providing accurate and relevant data in accordance with Islamic sharia principles. The use of technology in the Industry 4.0 era, including digital wallet applications, has made it easier to efficiently manage infaq funds and allows real-time communication. The use of digital payment methods, such as QRIS, further expands the reach and efficiency of fundraising, enabling donations via QR code scanning with common payment applications.